Long-term prognosis of conservatively managed traumatic pulp-exposed tooth fractures. - A/Prof Gajanan Kulkarni (Elsevier, 2023)
Introduction: Fractures of permanent anterior teeth with pulp exposure in children pose unique treatment challenges related to the management of the pulp and the restoration of the tooth. Case Description: A healthy 12-year-old female presenting with the chief complaint of fractured permanent anterior teeth several hours after an accident. The maxillary right central incisor (CI) had a large crown fracture with approximately 2 mm of pulp exposure and the right lateral incisor (LI) a fracture into dentin. The larger CI fragment of the tooth was brought in by the patient; the smaller LI was lodged in the lower lip. Anterior occlusal and lip radiographs confirmed the extent of the CI and LI crown fractures and the location of the fragment in the lip. Treatment included re-attachment of the larger CI fragment without any pulp treatment. The LI was similarly treated with re-attachment of the fragment immediately following its retrieval from the lip. The lip lesion was treated with primary closure of the incision site. The traumatized teeth remain vital, fully functional and asymptomatic for > 3-year follow up period. Discussion: While conventional treatments would require partial pulpotomies or pulpectomies or RCT and large restorations, we propose conservative approaches that can be attempted first. Conclusion/Clinical Significance: This case and other similar cases demonstrate that conservative treatment options that maintain pulp vitality in permanent teeth of young, mixed, -early-permanent- dentition stage children, are physiologically preferable, less invasive and financially advantageous to the patients and are viable long-term. Failures of the conservative treatments can always be remedied with conventional, more invasive options.